THE DEVELOPMENT OF HUMAN CAPITAL IN A KNOWLEDGE ECONOMY - E. D. Katulsky (Modernizaciâ, Innovaciâ, Razvitie, 2015)
Today, the progress of civilization becomes defined intellectual and educational power of man. Human capital because of its immensity become a major national resource. From the point of view of development, knowledge serves as a condition of social progress, as a prerequisite for public self-reflection, which in turn determines the level of the social system. The article discusses the theoretical aspects of the development of human capital in terms of the knowledge economy.